Impact of brand equity on purchase intent in sales promotion campaigns, with perceived value as the mediator - Shang, Yue (2023)
People are surrounded by advertisements of promotional offers online, but the effectiveness of these offers remains doubtful. This study explores the mechanism on how brand equity, with its measures like brand awareness, brand association, perceived quality and brand loyalty, impacts consumers’ purchase intent. A consumer electronic brand whose main products are smart phones was chosen and their online forum members were the respondents. This study is quantitative research with help with a questionnaire. The variables were either rated on a scale of numbers or later coded as numbers. A total of 91 valid answers were gathered and analysed. The empirical results of this study confirm the past literature that brand equity is significantly related to purchase intent across most of promotional campaigns, except for the between-brand freebie bundles. Perceived acquisition value and perceived transaction value fully mediate this total effect between brand equity and purchase intent; and the difference between strength of two mediators is subtle. In addition, the result shows that in the campaigns including only the products from the focal brand and a clear messaging, people’ responses show more reliable difference.